STUDENTS' PERCEPTIONS OF THE USE OF SPEECH RECOGNITION TECHNOLOGY IN ENGLISH LEARNING - Amirah Siregar, Ayunda Putri; Lubis, Yani (Universitas Pakuan, 2025)
The global demand for English language proficiency continues to grow significantly, particularly in the contexts of international communication, education, and the workforce. However, in Indonesia, many students still face difficulties in mastering English pronunciation due to limited interaction with native speakers and insufficient access to interactive learning tools. Speech Recognition Technology (SRT) has emerged as an innovative solution, offering real-time feedback and facilitating more adaptive, autonomous learning. One SRT tool gaining attention is the Cambridge Learning Dictionary (CLD). This study aims to analyze students' perceptions of using CLD in English language learning at Universitas Islam Negeri Sumatera Utara. Employing a qualitative phenomenological approach, the study involved ten female students aged 21–22 from the English Education Study Program. Data were collected through classroom observation, semi-structured interviews, and open-ended questionnaires. The findings indicate that most participants perceived the use of CLD positively, particularly in enhancing pronunciation accuracy, boosting speaking confidence, and fostering learner autonomy. Furthermore, three main themes emerged: (1) improved language competence through native-speaker pronunciation models in both British and American accents; (2) increased independent learning through self-directed use of CLD; and (3) technical challenges, including connectivity issues, the absence of real-time feedback, and the limited inclusion of Islamic vocabulary. Overall, CLD is considered to hold strong potential in supporting English learning in Islamic higher education settings, especially in terms of pronunciation and communicative skill development. To maximize its effectiveness, infrastructural support, formal training, and contextual content integration tailored to the cultural identity of Islamic educational institutions are recommended.